The impact of ESG risks on bank stability in Indonesia - Felisitas Defung; Rizky Yudaruddin; Nita Priska Ambarita; Norliza Che-Yahya; Nur Zahidah Bahrudin (Banks and Bank Systems)
The influence of Environmental, Social, and Governance (ESG) risks on bank stability has become a critical area of study in the banking sector. This study examines the influence of ESG risks on bank stability using unbalanced panel data from 134 commercial banks in Indonesia from 2003 to 2022. Employing a fixed effects model, the findings reveal a significant negative effect of ESG risks on bank stability, where higher ESG risks significantly reduce bank stability. Specifically, government-owned banks face a greater stability decline than private banks due to their often higher exposure to regulatory and reputational pressures. Smaller banks are more adversely affected than larger ones because they lack the resources and diversification to effectively mitigate ESG risks. Additionally, non-listed banks experience a larger decrease in stability than listed banks, as the latter tend to have stricter governance structures and more robust risk management practices. These findings underscore the need for tailored risk management strategies to address ESG risks, particularly for government-owned, smaller, and non-listed banks.